New aspects of gliatilin’ application for treating of patients with mild cognitive impairment - S. M. Moroz; A. G. Kirichenko; I. V. Rozhkova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The term «MCI» (MCI) denote the condition characterized by disturbance, at least one of the characteristics of cognitive sphere, it does not lead to the violation of autonomy in daily life, so it created the modern concept of mild cognitive decline «mild cognitive impairment» (MCI) identificeret category of patients with intermediate stage between normal age and dementia. In patients with light cognitive disorder (MCI) restoration and improvement of intellectual abilities significantly faster and was more pronounced in the group treated with gliatilin. Gliatilin application in complex therapy of discirculatory encephalopathy improves locomotor, neural, and cognitive function. The drug is well tolerated, does not cause undesirable effects, which is very important when treating patients of advanced age.